APLIKASI MESIN SANGRAI DENGAN BAHAN BAKAR BIOGAS UNTUK HOME INDUSTRY - Atmika, I.K.A; Nindhia, T.G.T.; Astawa, I.P.A.; Suriadi, I.G.A.K.; Surata, I.W. (Buletin Udayana Mengabdi, 2023)
The Pitik Jaya Women Farmers Group (KWT) is a business group located in Baluk village which is classified as a home business or home industry. This business group produces several types of products including; shredded eggs, flavored salted peanuts and others. In running its business, KWT faces a number of problems, especially for the production of the flavored salted peanuts. This problem is caused by the process of roasting peanuts using a rolling machine which is relatively simple with a limited capacity made from steel plates and is easily corroded and the spices are still stirred manually so it is uneven. Another problem is related to the high cost of LPG fuel used to heat the roaster. Based on this situation and to overcome these problems, the community service team designed and manufactured a roasting machine with biogas fuel. The field service activity (KWT Pitik Jaya) was carried out on August 22, 2021 in the form of an introduction and demonstration of a biogas-fired roasting machine. Next, on August 29, 2021, a safety demonstration was held and the official handover of the machine was attended by members of the Pitik Jaya KWT, the dedication team, Engineering students from the Udayana University Mechanical Engineering Study Program and Baluk village officials. The use of this biogas-fired roasting machine plays a very important role in increasing the production of flavored salted peanuts which reaches 320% or more than three times, as well as fuel cost efficiency reaching 90%, because it no longer uses LPG. Keywords : roasting machine, salted peanuts, biogas, increased production.